Peningkatan Teknik Dasar Tolak Peluru Menggunakan Modifikasi Peluru Melalui Lesson Study Pada Siswa Kelas V SDN 4 Karangrejo - Riska Fita Lestari; lutfi Irawan Rahmat; Edi Irwanto; Winarto (MAN Insan Cendekia Jambi, 2025)
The problem in this study is the still low basic shot-put-sport technique in grade V students of SDN Karangrejo Banyuwangi. This study aims to improve shot-put-sport learning with shot modification through Lesson Study in grade V students of SDN Karangrejo Banyuwangi Regency in 2023/2024. It is hoped that with this learning modification, the basic shot-put-sport technique will improve. This research is a Classroom Action Research. The research subjects used were 20 grade V students. This research was conducted in two cycles. Data taken by researchers and collaborators using student behavior observation sheets in learning and basic shot-put-sport movement assessment rubrics. The data obtained were analyzed using descriptive analysis. Based on the results of the research and discussion, it can be concluded that after being given the first cycle learning completeness action, the first meeting increased by 8.33% from the initial condition. In the first cycle, the second meeting increased by 37.50% from the first meeting. In the second cycle, it increased by 16.67% from the first cycle, the second meeting or increased by 62.50% from the initial condition. The improvement of learning completeness, the researcher believes that through the play approach, it is very helpful in the learning process of linear style shot put. Based on the results of the research and discussion that have been described in the previous chapter, the following conclusions can be drawn: by modifying shot put learning through Lesson study, it can improve the basic shot-put-sport technique in class V of SDN Karangrejo.